2013
DOI: 10.1016/s0924-9338(13)76515-5
|View full text |Cite
|
Sign up to set email alerts
|

1494 – Mindfulness-based cognitive therapy reduces depression symptoms in people who have a traumatic brain injury: results from a randomized controlled trial

Abstract: IntroductionTraumatic brain injuries (TBI) may lead to persistent depression symptoms. We conducted several pilot studies to examine the efficacy of mindfulness-based interventions to deal with this issue; all showed strong effect sizes. The logical next step was to conduct a randomized controlled trial (RCT).ObjectiveWe sought to determine the efficacy of mindfulness-based cognitive therapy for people with depression symptoms post-TBI (MBCT-TBI).MethodsUsing a multi-site RCT design, participants (mean age = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…Average baseline BDI‐II scores for the TBI‐plus‐depressive symptoms group was approximately 24, corresponding to moderate depressive symptoms (Figure a). These baseline BDI–II scores were comparable to previous studies in psychological intervention for depression in TBI (Ashman et al, ; Bédard et al, ; D'Antonio et al, ). Baseline BDI–II scores for the TBI‐only group (7.0) was higher than those of healthy individuals (3.6) from a previous study (Han et al, ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Average baseline BDI‐II scores for the TBI‐plus‐depressive symptoms group was approximately 24, corresponding to moderate depressive symptoms (Figure a). These baseline BDI–II scores were comparable to previous studies in psychological intervention for depression in TBI (Ashman et al, ; Bédard et al, ; D'Antonio et al, ). Baseline BDI–II scores for the TBI‐only group (7.0) was higher than those of healthy individuals (3.6) from a previous study (Han et al, ).…”
Section: Resultssupporting
confidence: 86%
“…(Figure 1a). These baseline BDI-II scores were comparable to previous studies in psychological intervention for depression in TBI (Ashman et al, 2014;B edard et al, 2014;D'Antonio et al, 2013). Baseline BDI-II scores for the TBI-only group (7.0) was higher than those of healthy individuals (3.6) from a previous study (Han et al, 2015).…”
Section: Demographicssupporting
confidence: 82%
“…Consistent with results from preliminary studies in TBI populations, 23,28,31,32 we found CBT-IP and, particularly, CBT-T are acceptable and feasible in a geographically diverse sample with complicated mild to severe TBI. There were no statistically significant differences between CBT treatments overall compared with UC on the primary outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…[26][27][28][29] Structural equation modeling has shown that post-TBI depression is consistent with cognitive behavioral theory, 30 and preliminary CBT trials have been promising for decreasing depressive symptoms. 23,28,31,32 The model of treatment delivery is crucial, because of the tremendous barriers to receipt of adequate mental health services. [33][34][35][36][37] Barriers for people with TBI include stigma; difficulty coordinating care for multiple medical and psychological problems; limited transportation (e.g., because of cost, distance, seizure disorder with inability to drive); avoidance of trauma-focused components of mental health care; and other motivational (ambivalence), behavioral, cognitive, social, and financial problems that interfere with their ability to attend scheduled appointments.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary MBCBT trials among people with TBI and symptoms of depression suggest this treatment may be efficacious. 6163 …”
Section: Discussionmentioning
confidence: 99%